2016
DOI: 10.1016/j.apjtm.2016.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance Acinetobacter species at the intensive care unit, Aseer Central Hospital, Saudi Arabia: A one year analysis

Abstract: Acinetobacter species including A. baumannii were found MDR (98.1%) according to the current Acinetobacter spp. antimicrobial categorization. Approximately half of these strains were A. baumannii. All Acinetobacter species were 100% sensitive to colistin and to some extent to trimethoprim + sulfamethoxazole (74.5%). ICU-acquired pneumonia among patients over 60 years of age who spend prolong times at artificial ventilations made up the majority of the cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 22 publications
5
30
0
1
Order By: Relevance
“…In our study it was found a very high level of resistance of Acinetobacter strains to the carbapenems, cephalosporins, piperacillin-tazobactam and ciprofloxacin, which is consistent with the results from other studies [3,[44][45][46]. Antimicrobial resistant Acinetobacter spp is a public health concern due to the severe limitation of treatment and infection control options [38].…”
Section: Resultssupporting
confidence: 92%
“…In our study it was found a very high level of resistance of Acinetobacter strains to the carbapenems, cephalosporins, piperacillin-tazobactam and ciprofloxacin, which is consistent with the results from other studies [3,[44][45][46]. Antimicrobial resistant Acinetobacter spp is a public health concern due to the severe limitation of treatment and infection control options [38].…”
Section: Resultssupporting
confidence: 92%
“…A high resistance to the carbapenems (73%) was found for the Acinetobacter strains, which were also resistant to cefotaxime (86%), cefepime (75.43%), ciprofloxacin (77.19%) and ceftazidime (66.66%). In another research conducted in Saudi Arabia on multidrug resistance Acinetobacter species at the intensive care unit, it was found a much higher percentage -over 90% -of resistant strains to the same antibiotics [30].…”
Section: Resultsmentioning
confidence: 94%
“…[131415161718] All these factors, as well as clonal dissemination, likely contributed to the increased prevalence of IRABC and XDRAB. [192021] In the present study, among the 2917 A. baumannii strains isolated, 1276 (43.7%) XDRAB strains were detected.…”
Section: Discussionmentioning
confidence: 99%